EFFECT OF NIFEDIPINE GITS VERSUS RAMIPRIL ON HOME BLOOD PRESSURE VARIABILITY: PRELIMINARY RESULTS OF REVERENT RANDOMIZED TRIAL. (April 2021) - Bilo, Grzegorz; Kyriakoulis, Konstantinos; Liu, Chang -Yuan; Soranna, Davide; Ceravolo, Isabella; Cassago, Silvia; Zhang, Wei; Kollias, Anastasios; Pengo, Martino; Zambon, Antonella; Wang, Jiguang; Stergiou, George S.; et al.
Abstract : Objective: Blood pressure (BP) variability (BPV) was shown to independently predict adverse outcomes, making it a potential target for treatment. Preliminary data indicated a possible larger reduction of BPV with dihydropyridine calcium channel blockers (CCB). However, it is not clear whether different antihypertensive drug classes can differently affect BPV. Aim of REVERENT (Reducing blood pressure Variability in Essential hypertension with Ramipril vErsus Nifedipine GITS) Trial was to compare BPV changes after a period of treatment with a CCB (nifedipine GITS) or an ACEI (ramipril). Design and method: Patients with essential hypertension either treatment naïve or after washout from previous treatment were included. Participants were randomized according to a PROBE design to nifedipine GITS 30 mg or ramipril 10 mg in a single morning dose. We report preliminary data on day-to-day BPV (expressed as standard deviation; SD of all readings) estimated from home measurements (7 days; duplicate morning and evening measurements per day; AND UA-651BLE) at baseline and after 10 weeks of treatment. Figure. No caption available. Results: 153 patients successfully completed the study (table). Patient characteristics, home BP and BPV values at baseline and after 10-week treatment in all participants and separately in naïve (N = 121) and previously treated patients (N = 32) are reported (table). We observed no significant differences between treatment groups in the change (baseline to 10-week) of home BPV except for treatment naïve hypertensive patients in whom a small but significant difference in systolic BPV change was observed. Conclusions: These data, overall, did not show clear differences between nifedipine GITS and ramipril in reducing home BPV, except for treatment-naïve individuals in whom a small but significant difference in favour of the CCB was observed. The relevance of treatment induced BPV changes requires documentation in outcome studies.